Analytical modeling of Cosmic Winds and Jets - Vlahakis, Nektarios (Ph.D. Thesis, 1998)
A widespread phenomenon in astrophysics is the outflow of plasma from the environment of stellar or galactic objects. This plasma outflows range from nonuniform winds to highly collimated jets which are common to many stages of stellar evolution. For example, collimated outflows are found around young stars (e.g., as in HH 30), older mass losing stars (as in eta-Carinae), symbiotic stars (e.g. in R Aqr), planetary nebulae nuclei (as in the hourglass nebula), black hole X-ray transients (as in GRS 1915+105 and GRO J1655-40), low- and high-mass X-ray binaries and recently also in cataclysmic variables (e.g. T Pyxidis). Similarly, they are also found emerging from the nuclei of many radio galaxies and quasars. Nevertheless, despite their abundance the questions of the formation, acceleration and propagation of nonuniform winds and jets have not been fully resolved. One of the main difficulties in dealing with the theoretical problem posed by cosmical outflows is that their dynamics needs to be described - even to lowest order - by the highly intractable set of the MHD equations. As is well known, this is a nonlinear system of partial differential equations with several critical points, and only very few classes of solutions are available for axisymmetric systems obtained by assuming a separation of variables in several key functions. This hypothesis allows an analysis in a 2-D geometry of the full MHD equations which reduce then to a system of ordinary differential equations. By a systematic method we construct general classes of exact and self-consistent axisymmetric MHD solutions. The unifying scheme contains three large groups of exact MHD outflow models, (I) meridionally self-similar ones with spherical critical surfaces, (II) radially self-similar models with conical critical surfaces and (III) generalized self-similar models with arbitrary shape critical surfaces. This classification includes known polytropic models, such as the classical Parker description of a stellar wind and the Blandford and Payne (1982) model of a disk-wind; it also contains nonpolytropic models, such as those of winds/jets in Sauty and Tsinganos (1994), Lima et al (1996) and Trussoni et al (1997). Besides the unification of all known cases under a common scheme, several new classes emerge and some are briefly analyzed; they could be explored for a further understanding of the physical properties of MHD outflows from various magnetized astrophysical rotators. We also propose a new class of exact and self-consistent MHD solutions which describe steady and axisymmetric hydromagnetic outflows from the magnetized atmosphere of a rotating gravitating central object with possibly an orbiting accretion disk. The plasma is driven by a thermal pressure gradient, as well as by magnetic rotator and radiative forces. At the Alfvenic and fast critical points the appropriate criticality conditions are applied. The outflows start almost radially but after the Alfven transition and before the fast critical surface is encountered the magnetic pinching force bends the poloidal streamlines into a cylindrical jet-type shape. The terminal speed, Alfven number, cross-sectional area of the jet, as well as its final pressure and density obtain uniform values at large distances from the source. The goal of the study is to give an analytical discussion of the two-dimensional interplay of the thermal pressure gradient, gravitational, Lorentz and inertial forces in accelerating and collimating an MHD flow. A parametric study of the model is given, as well as a brief sketch of its applicability to a self-consistent modeling of collimated outflows from various astrophysical objects. For example, the obtained characteristics of the collimated outflow in agreement with those in jets associated with YSO's. General theoretical arguments and various analytic self-similar solutions have recently shown that magnetized and rotating astrophysical outflows may become asymptotically cylindrical, in agreement with observations of cosmical jets. A notable common feature in all such self-consistent, self-similar MHD solutions is that before final cylindrical collimation is achieved, the jet passes from a stage of oscillations in its radius, Mach number and other physical parameters. It is shown that under rather general assumptions this oscillatory behaviour of collimated outflows is not restricted to the few specific models examined so far, but instead it seems to be a rather general physical property of an MHD outflow which starts noncylindrically before it reaches collimation. It is concluded thence that astrophysical jets are topologically stable to small amplitude, time-independent perturbations in their asymptotically cylindrical shape. Also, similarly to the familiar fluid instabilities these oscillations may give rise to brightness enhancements along jets.
Keywords: Physics: Astronomy and Astrophysics